ANALISIS PERBANDINGAN KEHILANGAN PRATEGANG AKIBAT METODE STRESSING SATU ARAH DAN DUA ARAH PADA JEMBATAN BETON PRATEGANG - Rizkia, Selvia Rahma; Suyadi, Suyadi; Husni, Hasti Riakara (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
A prestressed concrete bridge is a construction structure bridging one location to another location and this is made by stressing strands with opposite force caused by the external loading. The stressing process can be done before the concrete is molded (pre-tensioning) and after the concrete is molded (post-tensioning). The stressing in the prestressed post-tensioning concrete can be done with two methods; the one way and two ways stressing. Stressing by using these two stressing methods may cause different prestress force loss in the concrete. The objective of this research was to find out the influence of one way and two ways stressing methods to the prestress force loss, analysis was conducted by estimating prestress forces, determining amounts and lines of stranded-wire tendons, estimating pre-stress force loss because of one way and two ways stressing methods and force controlling and deflection in the girder. This research used PC I girder, PC U girder, and box girder types. The analysis results showed that the prestress force loss in the one way stressing method in PC I girder was 30.826%, 30.3401% in PC U girder, and 31.885% in box girder. The prestress force loss in two ways stressing method was 29.8397% in PC I girder, 29.3169% in PC U girder, and 31.4955% in box girder. The conclusion was that the prestress force loss in the girder by using one way stressing method was bigger than in two ways stressing method.Keywords: prestress concrete, stressing method, one way, two ways.